2008
DOI: 10.1021/cm702547p
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelastic and Optical Properties of Thick Boride Templates on Silicon for Nitride Integration Applications

Abstract: We present a comparative study of the structural, thermoelastic, and optical properties of ZrB2 films grown on silicon with the corresponding bulk ZrB2 behavior. Thick ZrB2 films (up to 500 nm) with device quality morphological and structural properties were grown on Si(111) for potential integration of GaN with Si substrates. HR-XRD was used to analyze the thickness and temperature dependence of the films’ strain state. The data indicate that at room temperature a residual tensile strain of ∼0.5% persists in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…[22][23][24] Figure 4 shows the experimentally measured photoemission (PES) 28 and x-ray photoemission (XPS) 27 spectra of ZrB 2 compared with the calculated energy distribution of total DOS. The calculated DOS has been broadened to account for life-time effects and for the experimental resolution.…”
Section: B X-ray Absorption and Photoemission Spectramentioning
confidence: 99%
See 3 more Smart Citations
“…[22][23][24] Figure 4 shows the experimentally measured photoemission (PES) 28 and x-ray photoemission (XPS) 27 spectra of ZrB 2 compared with the calculated energy distribution of total DOS. The calculated DOS has been broadened to account for life-time effects and for the experimental resolution.…”
Section: B X-ray Absorption and Photoemission Spectramentioning
confidence: 99%
“…Experimentally the electronic structure of ZrB 2 and TiB 2 has been investigated by means of photoemission spectroscopy, 27,28 point contact spectroscopy, 33 x-ray absorption spectroscopy, 28,59 and optical spectroscopy. [22][23][24] Figure 4 shows the experimentally measured photoemission (PES) 28 and x-ray photoemission (XPS) 27 3). The major peak a close to the Fermi energy is derived by Zr 4d states.…”
Section: B X-ray Absorption and Photoemission Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…20 Since the infrared wavelengths are not sensitive to the surface, the thickness of the surface layer was kept fixed at $2 ffiffi ffi 2 p times the RMS value from AFM measurements. 21 We found that neglecting the surface layer from the model introduces an error of up to 20% in thickness and resistivity values of $3-4 nm shallow junctions. As a result, up to 6% error in R s can be observed.…”
mentioning
confidence: 84%